2011
DOI: 10.1007/s00276-011-0891-x
|View full text |Cite
|
Sign up to set email alerts
|

An aberrant cerebellar artery originating from the internal carotid artery

Abstract: The aberrant origin of the cerebellar arteries from anterior cerebral circulation is a quite rare vascular variation. Herein, we report a 52-year-old white female with angiographically occult subarachnoid hemorrhage. Left superior and anterior inferior cerebellar arteries were not detected. An aberrant cerebellar artery was noted to arise from the left cavernous internal carotid artery and terminated in the distribution of the ipsilateral superior and anterior inferior cerebellar arteries. This variant artery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In the present case, cerebellar infarcts without posterior circulation involvement can be explained by either petrosal sinus thrombosis [15] or presence of an aberrant cerebellar artery originating from cavernous part of internal carotid artery which represents persistence of fetal anterior and posterior circulation communications [16].…”
Section: Discussionmentioning
confidence: 67%
“…In the present case, cerebellar infarcts without posterior circulation involvement can be explained by either petrosal sinus thrombosis [15] or presence of an aberrant cerebellar artery originating from cavernous part of internal carotid artery which represents persistence of fetal anterior and posterior circulation communications [16].…”
Section: Discussionmentioning
confidence: 67%
“…Siqueira et al 3 reviewed 5500 angiographic studies over 4 years and found 11 cases of PTA variant (incidence of 0.18%). Shoja et al 4 reported a case of a 52-year-old white woman who presented with headache and subarachnoid haemorrhage; CTA revealed no aneurysm, however it demonstrated a left PTA originating from the cavernous ICA. Bykowski et al 5 also reported a case of PTA (type IIIb) associated with a cerebellar infarct in a patient who presented with dysmetria and gait imbalance.…”
Section: Descriptionmentioning
confidence: 99%
“…The study conducted considerably supplements existing data concerning the structure and topography of the carotid arteries during the fetal and early neonatal period of human ontogenesis, which is an essential constituent while making perinatal diagnostics and understanding real parameters of the norm and pathology [4,5,16,17,19,20]. The obtained new scientifically substantiated data concerning organometric characteristic of the carotid arteries at all the stages of the perinatal period determine morphological basis and are essential to determine developmental criteria of the carotid arteries and their correspondence to the terms of gestation [7,8,13,18].…”
Section: Introductionmentioning
confidence: 99%